Image dataset of benthic foraminifera taxa from Denmark Strait sediments on the northwestern Iceland slope (North Atlantic Ocean) - Liubov Kireenko; Anna Tikhonova; Nina Kozina; Alexander Matul (Data in Brief, 2022)
The article presents an image dataset of benthic foraminifera assemblage in long sediment core AMK-5890 obtained during the 71st cruise of the research vessel Akademic Mstislav Keldysh in summer 2018 from the northwestern Iceland slope in Denmark Strait (North Atlantic Ocean). In the area of study, dense cold water masses of the East Greenland Current from the Nordic Seas contact and mix with warm salty water of the Irminger Current from the North Atlantic Ocean creating specific conditions for the benthic microfauna habitat which reflect forming the lower link of the global thermohaline circulation. The benthic foraminifera assemblages are a reliable indicator for paleooceanographic and ecological reconstructions describing the environments on the bottom in present and past. In the core AMK-5890, the benthic foraminifera assemblage consists of 63 species some of which were combined into one genus (for example, Fissurina sp.). The dominants, subdominants and species list of benthic foraminifera changed within the core depth. This image dataset helps to fill the gaps in the practical micropaleontological analysis of benthic foraminifera giving better information for the species identification from the modern and Pleistocene sediments.